Teacher Training in Science for Citizenship: A Proposal Inspired by the Reggio Emilia Philosophy - Pezoa-Carrasco, Estefanía (2022)
Introduction. Education for citizenship should be developed from early childhood, considering the knowledge, attitudes, and values required for participation. One of the aspects contributing to this is scientific literacy through inquiry, for which there must be teachers who can integrate this aspect into didactic designs to allow democratizing scientific knowledge and favor the centrality and participation of children in basic education. Objective. To contribute to developing scientific inquiry in the training of future elementary school teachers. Discussion. In this perspective, the Reggio Emilia philosophy can contribute from its principles to the initial training of basic education teachers. For this purpose, three relevant aspects to incorporate are the environment as a third educator, classroom projects, and the teaching staff as a researcher reflected in the pedagogical documentation. With this, it is sought that inquiry is integrated as a methodological approach to be addressed in the training of teachers, promoting learning from experience. Conclusions. In this sense, from the three elements reviewed, we conclude that the Reggio Emilia philosophy is presented as an opportunity to improve inquiry skills and their incorporation into the future practices of elementary school teachers.